Po sledite na Levski i brtsk (Sofiya)
227 sayfa
Keywords: This volume includes Bulgarian translation together with transliteration and facsimiles of 36 archival documents preserved in the Ottoman Archive in İstanbul, Turkey. All of them comprise correspondence between the local and Central Ottoman authorities with regard to their efforts to prevent the seditious activity of the Bulgarian Revolutionary Central Committee in Bucharest, and the Internal Revolutionary Organization in Bulgaria led by Vasil Levski. The documents date from January 1872 to March 1874 and reveal that the Ottoman government was informed in detail about the revolutionary activities in the Bulgarian lands as late as September 1872. In terms of topic, the documents could be divided into the following groups : 1) documents revealing information about the persons, who were involved in the revolutionary organization, and the measures undertaken by the Ottoman authorities to detect and capture them; 2) documents related to the establishment of a special judicial commission to carry out the legal proceedings against the revolutionaries who were detained and prosecuted in Sofia; 3) documents dealing with the death sentences of the revolutionary leaders Vasil Levski and Dimitar Obshti; 4) documents about the career advancement and rewarding of Ottoman officials for their service in chasing the organization functionaries; 5) documents related to the recovery of financial resources spent out for uncovering and detaining these functionaries; 6) documents granting daily allowance for the revolutionaries who were exiled to Diyarbakır in Southeastern Anatolia.